(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article shows the directions of various parameters that affect the wheels of cars equipped with ABS and the dependence of the changes that occur during the braking process as a result of their influence on the braking path, as well as the mathematical models of the wheel. The four stages of the study are given and the stages of developing a model of wheel rotation during braking of a car equipped with ABS in the study of the kinematic model of elastic wheel rotation with a solid tire are correct. concepts are given.